SMALLER FORAMINIFERS, CHARACTERISTIC ALGAE AND PSEUDO-ALGAE OF THE LATEST CARBONIFEROUS-EARLY PERMIAN RATTENDORF GROUP,CARNIC ALPS (AUSTRIA/ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2001)
Limestones of the latest Carboniferous-early Permian Rattendorf Group (Lower Pseudoschwagerina Limestone, Grenzland Formation and Upper Pseudoschwagerina Limestone) of the Carnic Alps (Austria/Italy) contain a rich and interesting assemblage of smaller foraminifers, algae and pseudo-algae. The foraminiferal assemblage of the Lower Pseudoschwagerina Limestone is identical to that of the Auernig Formation. The Grenzland Formation is characterized by the appearance of the genus Geinitzinaand Pseudovermiporella, and the disappearance of Bradyinidae. The Upper Pseudoschwagerina Limestone contains the same species as the Grenzland Formation, but is characterized by the local appearance of Neoendothyra (?) and diverse species of Hemigordiidae and Nodosarioidea. The biostratigraphical value of diverse species of Hemigordius, ìArenovidalinaîsensu Baryshnikov = ìNeohemigordiusîsensu Pinard & Mamet, Nodosinelloides, Protonodosariaand Geinitzinafor the Asselian and early Sakmarian stages is briefly discussed. The systematical part contains some generic remarks on the Hemigordiidae and Nodosarioidea. Due to the porcelaneous wall, the microfossils Ellesmerellapermica(Pia) (= ìGirvanellaî subparallelaFlügel & Flügel-Kahler) and Pseudovermiporella spp., which are generally interpreted as algae, are considered as attached miliolinid foraminifera. A new genus of problematical Chlorophyta, Homannisiphon,is established.